Association analysis of rice resistance genes and blast fungal avirulence genes for effective breeding resistance cultivars - Tian, Dagang; Deng, Yun; Yang, Xiaoshuang; Li, Gang; Li, Qixiang; Zhou, Haiying; Chen, Ziqiang; Guo, Xinrui; Su, Yan; Luo, Yuming; Yang, Liming (Frontiers in Microbiology, 2022)
Utilization of rice blast-resistance (R) genes is the most economical and environmentally friendly method to control blast disease. However, rice varieties with R genes influence the outcome of genetic architectures of Magnaporthe oryzae (M. oryzae), and mutations in avirulence (AVR) genes of M. oryzae may cause dysfunction of the corresponding R genes in rice varieties. Although monitoring and characterizing rice R genes and pathogen AVR genes in field populations may facilitate the implementation of effective R genes, little is known about the changes of R genes over time and their ultimate impact on pathogen AVR genes. In this study, 117 main cultivated rice varieties over the past five decades and 35 M. oryzae isolates collected from those diseased plants were analyzed by PCR using gene-specific markers of the nine R genes and six primer pairs targeting the coding sequence or promoter of AVR genes, respectively. The R genes Pigm, Pi9, Pi2, Piz-t, Pi-ta, Pik, Pi1, Pikp, and Pikm were identified in 5, 0, 1, 4, 18, 0, 2, 1, and 0 cultivars, respectively. Significantly, none of these R genes had significant changes that correlated to their application periods of time. Among the four identified AVR genes, AVR-Pik had the highest amplification frequency (97.14%) followed by AVR-Pita (51.43%) and AVR-Pi9 (48.57%); AVR-Piz-t had the lowest frequency (28.57%). All these AVR genes except AVR-Pi9 had 1–2 variants. Inoculation mono-genic lines contained functional genes of Pi2/9 and Pik loci with 14 representative isolates from those 35 ones revealed that the presence of certain AVR-Piz-t, AVR-Pita variants, and AVR-Pik-E + AVR-Pik-D in M. oryzae populations, and these variants negated the ability of the corresponding R genes to confer resistance. Importantly, Pi2, Pi9, and Pigm conferred broad-spectrum resistance to these local isolates. These findings reveal that the complex genetic basis of M. oryzae and some effective blast R genes should be considered in future rice blast-resistance breeding programs.